2019
DOI: 10.1177/8756870519860514
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Federal Personnel Preparation Grants on Special Education Teacher Candidate Recruitment for Rural and Remote Alternative Teaching Pathways

Abstract: This article describes rural and remote teacher training in low incidence (LI) disabilities through an alternative teaching pathway (ATP) and the efforts of one university’s ATP program to address the ongoing critical special education teacher shortage in rural and remote school districts. The impact of the federal investment in recruiting/training teacher candidates in LI disabilities in rural and remote areas is described, and critical features of a distance education ATP programs in LI are discussed. Lesson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Another example of a successful ATP program that has been used to train rural and remote teachers is the University of Utah ATP program (Jameson et al, 2019). Coursework is delivered via distance technologies in both synchronous and asynchronous formats to provide high-quality instruction to students at a distance.…”
Section: Atp Programs To Address the Rural Teacher Shortagementioning
confidence: 99%
See 3 more Smart Citations
“…Another example of a successful ATP program that has been used to train rural and remote teachers is the University of Utah ATP program (Jameson et al, 2019). Coursework is delivered via distance technologies in both synchronous and asynchronous formats to provide high-quality instruction to students at a distance.…”
Section: Atp Programs To Address the Rural Teacher Shortagementioning
confidence: 99%
“…Over the last decade, more than 14 school districts across the state have participated in the ATP programs, many of which serve diverse and high-poverty areas. Jameson et al (2019) highlighted this program's use of federal grant funding, consistent communication using web-based technology, on-site coaching, and postgraduation mentorship to support teacher candidates in rural areas. In response to national and regional teacher shortages and in compliance with state regulations, the University of Louisville offers an ATP program in the area of MSD for the Grades P to 12 setting.…”
Section: Atp Programs To Address the Rural Teacher Shortagementioning
confidence: 99%
See 2 more Smart Citations
“…In a comprehensive search within special education (Day, 2022), no studies were found that examined special education teacher preparation regarding: (a) national AR policy trends or (b) the comprehensive preparation characteristics of AR IHEs and AR non-IHEs within the United States. However, several studies examined special education teacher preparation within AR programs for smaller geographic regions (Jameson et al, 2019; Robertson & Singleton, 2010; Scott et al, 2019). Other research in this field examined the effectiveness of ARs contributing to the special education teacher pipeline in a specific locality (e.g., one city, state, region within a state), revealing that the effectiveness of specific AR programs depended on their program infrastructure and program requirements (Rosenberg et al, 2007; Sindelar et al, 2012).…”
Section: Accountability Reporting Mandatesmentioning
confidence: 99%